Inhibitory Neural Regulation of the Ca2+ Transients in Intramuscular Interstitial Cells of Cajal in the Small Intestine - Baker, Salah A.; Drumm, Bernard T.; Cobine, Caroline A.; Keef, Kathleen D.; Sanders, Kenton M. (Frontiers in Physiology, 2018)
Gastrointestinal motility is coordinated by enteric neurons. Both inhibitory and excitatory motor neurons innervate the syncytium consisting of smooth muscle cells (SMCs) interstitial cells of Cajal and PDGFRα+ cells (SIP syncytium). Confocal imaging of mouse small intestines from animals expressing GCaMP3 in ICC was used to investigate inhibitory neural regulation of ICC in the deep muscular plexus (ICC-DMP). We hypothesized that Ca2+ signaling in ICC-DMP can be modulated by inhibitory enteric neural input. ICC-DMP lie in close proximity to the varicosities of motor neurons and generate ongoing Ca2+ transients that underlie activation of Ca2+-dependent Cl- channels and regulate the excitability of SMCs in the SIP syncytium. Tetrodotoxin increased Ca2+ transients in ICC-DMP, demonstrating that these cells participate in tonic inhibition. Electrical field stimulation (EFS) caused inhibition of Ca2+ for the first 2-3s of stimulation, and then Ca2+ transients escaped from inhibition. The NO donor (DEA-NONOate) inhibited Ca2+ transients and Nω-Nitro-L-arginine (L-NNA) or a guanylate cyclase inhibitor (ODQ) blocked inhibition induced by EFS. Purinergic neurotransmission did not affect Ca2+ transients in ICC-DMP. Purinergic neurotransmission elicits hyperpolarization of the SIP syncytium by activation of K+ channels in PDGFRα+ cells. Generalized hyperpolarization of SIP cells by pinacidil (KATP agonist) or MRS2365 (P2Y1 agonist) also had no effect on Ca2+ transients in ICC-DMP. Peptidergic transmitter receptors (VIP and PACAP) are expressed in ICC and can modulate ICC-DMP Ca2+ transients. In summary Ca2+ transients in ICC-DMP are blocked by enteric inhibitory neurotransmission. ICC-DMP lack a voltage-dependent mechanism for regulating Ca2+ release, and this protects Ca2+ handling in ICC-DMP from membrane potential changes in other SIP cells.